The impact of World War Two and rationing on U.K. expenditure in the short and long run - Adrian R. Fleissig (The Journal of European Economic History, 2020)
World War Two, rationing, and shortages limited the amount of food and other goods available to households. The new welfare state of Clement Attlee's Labour Party and derationing were supposed to provide food and other consumption goods to meet the needs of households, but voters were dissatisfied. Churchill's Conservative Party, with a campaign promising to end rationing quickly, regained power. It is unclear how rationing affected households' expenditure adjustments in the short and long run. Our results show that income and own-price elasticities varied considerably in both the short and long run before, during and after the war. Varying elasticities provide insight into how households adjusted their expenditures over time. Food is typically an essential consumption item, but estimates show it was almost a luxury good during the war and in the postwar period. There is evidence that households were unable to make typical long-run desired expenditure adjustments during the war and for some time after it. Binding food rationing significantly affected spending on other goods and services. Rationing had a severe impact on household expenditures. The campaign to end rationing was pivotal in the Conservatives Party's landslide victory.
Keywords: 330